2021
DOI: 10.22207/jpam.15.3.58
|View full text |Cite
|
Sign up to set email alerts
|

Malathion Biodegradation by L. casei (NRRL1922) and L. acidophilus (NRRL 23431) in Fermented Skimmed Milk

Abstract: The aim of this study was to investigate and trace the biodegradation products of the pesticide malathion in a comparative manner by two different lactobacilli strains; L. casei (NRRL1922) and L. acidophilus (NRRL 23431). The two strains were cultivated separately into skimmed milk supplemented with 5 ng/ml malathion. After incubation under the appropriate conditions, randomized samples were taken at intervals 24, 48, 72 and 120 hours along with control samples and analyzed for the presence of malathion and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies on tomato juice containing such bacteria have shown that this product can serve as a healthy drink for vegetarians or consumers who are allergic to dairy products [ 122 ]. The beneficial effects of the L. acidophilus [ 120 , 128 , 129 ], Lcb. casei and Lcb.…”
Section: Probioticsmentioning
confidence: 99%
“…Studies on tomato juice containing such bacteria have shown that this product can serve as a healthy drink for vegetarians or consumers who are allergic to dairy products [ 122 ]. The beneficial effects of the L. acidophilus [ 120 , 128 , 129 ], Lcb. casei and Lcb.…”
Section: Probioticsmentioning
confidence: 99%
“…However, their excessive and inconsiderate usage affects the environment and becomes one of the factors of climate change [1, 2]. For pests , control, an organophosphorus insecticide has been extensively applied [3]. Malathion is considered one of the first and most commonly used OP and is still used extensively in Egypt, especially for agriculture [4].…”
Section: Introductionmentioning
confidence: 99%